2011
DOI: 10.1007/s00894-011-1179-0
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorially-generated library of 6-fluoroquinolone analogs as potential novel antitubercular agents: a chemometric and molecular modeling assessment

Abstract: The virtual combinatorial chemistry approach as a methodology for generating chemical libraries of structurally-similar analogs in a virtual environment was employed for building a general mixed virtual combinatorial library with a total of 53.871 6-FQ structural analogs, introducing the real synthetic pathways of three well known 6-FQ inhibitors. The druggability properties of the generated combinatorial 6-FQs were assessed using an in-house developed drug-likeness filter integrating the Lipinski/Veber rule-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
(70 reference statements)
1
29
0
Order By: Relevance
“…was equal to reference drug. The results were in accordance with the reported finding that one of the promising hits originated from moxifloxacin chemical class (22,23).…”
Section: Chemistrysupporting
confidence: 94%
See 1 more Smart Citation
“…was equal to reference drug. The results were in accordance with the reported finding that one of the promising hits originated from moxifloxacin chemical class (22,23).…”
Section: Chemistrysupporting
confidence: 94%
“…Several quinolone hybrids displayed enhanced antibacterial activity against both Grampositive and Gram-negative organisms (13)(14)(15)(16)(17)(18)(19)(20). Recently, chemometric studies coupled with 3D structure-based molecular modeling approaches were conducted to explore the possibilities for the optimization of quinolone compounds, which also revealed that several novel fragments attached at 1 and 7 positions of those quinolones Research Article could provide a good accommodation for binding of the active site (22,23). All these stimulated us with great interest to focus on further structural modification at the C-7 position of quinolone in order to find novel quinolone derivatives with potential activity against bacterial strains including drug-resistant microorganisms.…”
mentioning
confidence: 98%
“…Conversely, the CombiLib library consisting of 427 drug‐like 6‐FQs (R 1 , R 7 ‐structural analogs of ciprofloxacin and moxifloxacin, as well as R 7 ‐structural analogs of ofloxacin) was obtained by using classical methodology for virtual combinatorial library design. [31, 32] The details of both libraries were discussed previously[28, 30] and therefore we give here only a brief summary.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The validated protein model with highest estimated discriminatory performances was subsequently used for generating the binding poses of a mixed virtual combinatorial drug‐like set of 427 analogs for which the biological activity values were predicted by using nonlinear chemometric strategy. [28]…”
Section: Introductionmentioning
confidence: 99%
“…1.1a). Combinatorial chemistry has also led to the development of novel antibiotics against S. aureus such as 3-aminoquinazolinediones (Hutchings et al 2008) or 6-fluoroquinolones (Ghosh and Bagchi 2011;Minovski et al 2012) active against Mycobacterium tuberculosis ( Fig. 1.1b).…”
Section: Introductionmentioning
confidence: 99%